Efficacy of a Pineapple Core-Based Hand Sanitizer in Reducing Bacterial Contamination and Infection Risk in Diabetic Foot Ulcer Care: A True Experimental Study - Sukron Sukron; Heri Shatriadi; Indah Sari; Nichapatr Phutthikhamin (Media Publikasi Cendekia Indonesia, 2026)
This study evaluated the efficacy of a natural hand sanitizer derived from pineapple core extract as an alternative to alcohol-based agents for reducing bacterial contamination and infection risk during diabetic foot ulcer (DFU) care. Using a true experimental design, the researchers conducted microbiological assessments of 16 nurse hand swabs and clinical observations of 43 DFU patients between February and April 2025. Microscopic results revealed a significant reduction in bacterial presence: only 18.75% of swabs tested positive for gram-positive cocci with the pineapple-based sanitizer, compared to 68.75% in the control group. Furthermore, clinical findings indicated that 76.74% of patients remained infection-free following wound care procedures employing the extract. The study concludes that pineapple core extract possesses potent antimicrobial and anti-inflammatory properties, largely attributed to the enzyme bromelain, making it a viable, eco-friendly, and cost-effective alternative for infection control in specialized wound care settings